Modern art, 1851-1929 : capitalism and representation - Brettell, Richard R. (Oxford ; New York : Oxford University Press, 1999)
"Richard Brettell's innovative account explores the aims and achievements - the beautiful and the bizarre - of artists such as Monet, Gauguin, Picasso, and Dali, in relation to urban capitalism and expansion, colonialism, nationalism and internationalism, and the museum. Tracing common themes of representation, imagination, perception, and sexuality across works in a wide range of different media, he presents a fresh approach to the fine art and photography of this remarkable era."--Jacket.
Introduction: The Great Exhibition of 1851, London -- Paris: the capital of modern art -- New technology -- The beginnings of modern art -- Realism to Surrealism -- Realism -- Impressionism -- Symbolism -- Post-Impressionism -- Neo-Impressionism -- Synthetism -- The Nabis -- The Fauves -- Expressionism -- Cubism -- Futurism -- Orphism -- Vorticism -- Suprematism/Constructivism -- Neo-Plasticism -- Dada -- Purism -- Surrealism -- The '-ism' problem -- The Conditions for Modern Art -- Urban Capitalism -- Paris and the birth of the modern city -- Capitalist society -- The commodification of art -- The modern condition -- Modernity, Representation, and the Accessible Image -- The art museum -- Temporary exhibitions -- Lithography -- Photography -- The Artist's Response -- Representation, Vision, and 'Reality': The Art of Seeing -- The human eye -- Transparency and unmediated modernism -- Surface fetishism and unmediated modernism -- Photography and unmediated modernism -- Beyond the oil sketch -- Cubism -- Image/Modernism and the Graphic Traffic -- The Pre-Raphaelite brotherhood -- Puvis de Chavannes and Gustave Moreau: image/modernism outside the avant-garde -- Image/modernism outside France -- Exhibitions of the avant-garde -- Fragmentation, dislocation, and recombination -- Iconology -- Sexuality and the Body -- Manet's bodies -- Modern art and pornography -- The nude and the modernist cycle of life -- The bathing nude -- The allegorical or non-sexual nude -- Colonialism and the nude: the troubled case of Gauguin.
Includes bibliographical references (pages 218-225) and index.
Keywords: Art, European -- 19th century; Art, European -- 20th century